ORAL THRUSH IN PREGNANT WOMEN: CAUSES, RISKS AND PREVENTION STRATEGIES - Alina Mihaela Calin; Nicolae Sarbu; Gabi Topor; Iulian Catalin Bratu; Victorita Stefanescu; Simona Parvu; Silvia Nica; Denisa Batir Marin; Doriana Agop Forna; Iulia Alecsandra Salcianu (Romanian Society of Oral Rehabilitation, 2024)
Canker sores are a common condition among pregnant women, having a significant impact on oral and overall health. This article explores the causes, risks, and prevention strategies associated with mouth sores during pregnancy. Hormonal changes, weakening of the immune system, and stress are relevant factors in their occurrence. Risks include physical and emotional discomfort, as well as possible pregnancy complications. Proper oral hygiene, balanced nutrition, and stress reduction are essential strategies for preventing oral thrush. Treatment during pregnancy requires a gentle approach, and treatment options must be safe for the mother and baby. In conclusion, proper management of mouth sores during pregnancy is essential for the oral and general health of pregnant women and the fetus. The use of transdermal systems for administering crucial oils to pregnant women is an innovative and effective method of treatment of canker sores in pregnant women, offering multiple benefits and ensuring increased safety for mother and baby.